Helping the Samanis and Gaznas of the Scientists - Muzafar Esmahil Ali; Omid Ibrahim (QALAAI ZANIST JOURNAL, 2023)
Interest of scientists in both emirates samanids and Ghaznawid clearly appeared after they were able to establish a, peaceful and secure country, helping scientists by the princes of Samanids and Ghaznawid sultans was a main factor of emerging great scientists among them the Biruni and al- Khwarizmi and others prominent figures. these scientists played a huge role in stages of history and became source of scientific and historical research for their future generation.